Ophiocordyceps : Fungi Entomopatogen Penyebab Zombie Pada Serangga - Putra, Ivan Permana (Universitas Muhammadiyah Surakarta, 2021)
Ophiocordyceps is special type of entomopathogenic fungi which well known to infect insects and turning them into zombie. A total of 250 species have been described from its genus, and some are known to control their hosts, which are most notably ants. They are ubiquitous within tropical rain forests across the board, with few publication reports from temperate ecosystems. These fungal pathogens possess the capacity to manipulate host behaviour in order to increase their own ﬁtness. These entomopathogenic fungi cause their hosts frezee to die in an exposed area on the abaxial surface of leaves or branches, which then enhancing the fungus spore production and dispersal. Despite the high diversity of fungi and insect with vast tropical forest as well as drugs potency from Ophiocordyceps, publication of Ophiocordyces was rarely reported from Indonesia. This review will explain the evolution of Ophiocordyceps-insect interaction, simbiont distribution, and zombie-insect formation mechanism, in order to induce zombie-insect research in Indonesia.